2019
DOI: 10.3390/ani9030115
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly (Hermetia Illucens) as Dietary Source for Laying Quails: Live Performance, and Egg Physico-Chemical Quality, Sensory Profile and Storage Stability

Abstract: Insects are promising candidates as alternative sustainable sources of protein for poultry species. The present research studied the effect of a dietary inclusion of a defatted black soldier fly (BSF) larvae meal as an alternative protein source in the diets of laying quails, on productive performance, egg physicochemical quality, fatty acid profile, sensory traits and storage stability. A total of 225 laying quails were divided into 3 dietary groups (5 replicates/each). A conventional soybean meal-based diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
8
35
0
1
Order By: Relevance
“…The only available results deal with laying poultry species. In laying quails fed with defatted HI larvae meal (10% or 15% inclusion levels), eggs did not display a reduction in their cholesterol content [29] consistent with the fact that most animal species, including birds, have tight cholesterol regulation. In contrast, Secci et al [30] found that laying hens fed with HI larvae meal as a 100% replacement for soybean meal showed the lowest cholesterol content in the egg yolk.…”
Section: Discussionmentioning
confidence: 85%
“…The only available results deal with laying poultry species. In laying quails fed with defatted HI larvae meal (10% or 15% inclusion levels), eggs did not display a reduction in their cholesterol content [29] consistent with the fact that most animal species, including birds, have tight cholesterol regulation. In contrast, Secci et al [30] found that laying hens fed with HI larvae meal as a 100% replacement for soybean meal showed the lowest cholesterol content in the egg yolk.…”
Section: Discussionmentioning
confidence: 85%
“…Insects are potentially highly sustainable as they are poikilothermic and characterised by a high feed conversion efficiency, they require low amounts of water and land to be farmed, and many of them can be successfully grown on organic side streams, converting low-value organic by-products into highvalue protein (van Zanten et al 2014) In parallel, insects, which can either be used as a whole or being separated into protein meal and fat, are excellent sources of nutrients: in general, they have a high protein content with a nutritive value similar to soybean meal, they are good sources of fatty acids, vitamins and microminerals (Rumpold and Schl€ uter 2013). In recent years, most research efforts have been directed towards insect species such as the black soldier fly (Hermetia illucens), the housefly (Musca domestica) and the yellow mealworm (Tenebrio molitor): they generally provided positive outcomes when tested as part of diets intended for different poultry species (Pieterse et al 2014;Biasato et al 2016;Cullere et al 2016Cullere et al , 2018Dalle Zotte et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Three groups of insects including black soldier fly (Hermetia illucens), common housefly (Musca domestica), and yellow mealworm (Tenebrio molitor; TM) are species with the highest potential for largescale production to be used in diet of poultry (Veldkamp and Bosch 2015). There are many studies which supplemented insect meal in replace of fish meal or soybean meal in diet of broiler chickens (Biasato et al 2018), laying hens (Bovera et al 2018;Marono et al 2017), broiler quails (Shariat Zadeh et al 2019) and laying quails (Dalle Zotte et al 2019). Amao et al (2010) reported that westwood larva meal could be replaced up to 75% fishmeal in diet of laying hens.…”
Section: Introductionmentioning
confidence: 99%